Developing a Forest City in a New Capital City: A Thematic Analysis of the Indonesian Government’s Plans (Jurnal Bina Praja, 2023)
This study analyzes the Indonesian government's plans to develop a forest city in the new capital (IKN). This study uses a qualitative approach by examining several relevant official government documents. It is done by thematic analysis. The findings of this study indicate that the forest city development plan in IKN is based on the principles; of conservation of natural resources and wildlife habitats, connected with nature, low carbon development, development of water resources, controlled development, and community involvement. In addition, the government has also calculated the benefits gained from the development of the forest city economically, socially, and environmentally. However, the government cannot only calculate the benefits but also considers other negative aspects that could occur, such as forest ecosystem problems. Development that is not carried out carefully can cause environmental damage and threaten survival. This study encourages the government to act following an orientation towards quality and sustainable environmental management. This can only be done if the government implements strong and strict regulations. The government also needs to consider financial problems and socio-economic challenges. This is useful for ensuring sustainable development can run harmoniously between the government, the environment, and the social community.